Spinal myoclonus: a rare presentation of cervical myelopathy. (30th July 2018) - Christodoulides, Ioannis; Giamouriadis, Anastasios; Bashford, James; Barkas, Konstantinos
Abstract : Myoclonus describes a movement disorder characterised by brief, abrupt and involuntary contractions of muscles or groups of muscles, usually associated with intracranial lesions, with limited evidence linking it to spinal pathologies. The pathophysiology of spinal myoclonus is extensive and multifactorial. Infection, intramedullary and extramedullary space-occupying lesions, trauma, vascular abnormalities, degenerative processes and cervical spondylosis have been implicated with the disease, the latter been associated with cervical stenosis with no reported cases linking it to an underlying cervical disc herniation. Although medical therapy with clonazepam, levetiracetam, valproate, tetrabenazine hydrochloride and spinal block injections has been equivocal, spinal myoclonus secondary to disc herniation requires surgical intervention. This report describes a case of segmental spinal myoclonus, secondary to a herniated cervical intervertebral disc. After corpectomy and a cage-augmented fusion technique, the myoclonic symptoms resolved. To our knowledge, this was the first report to describe the successful management of discogenic spinal myoclonus with spinal surgery.